Proposing an Emergency Medicine Ethical Guideline; a Qualitative Study - Asadabadi, Leili; Soltani Nejad, Kamran; Zolfagharnasab, Atefeh; Mobasher, Mina (Archives of Academic Emergency Medicine, 2022)
Introduction: Emergency medicine physicians face major ethical challenges in their practices. Furthermore, they need to be aware of the principles of ethical analysis and clinical decision-making in order to provide quality care. This study aimed to propose professional ethics codes in the emergency medicine department. Method: This is a qualitative study, which was performed using narrative review and expert panel, and was conducted in three steps, including: literature review and preparation of the initial draft of the ethical concepts, obtaining expert opinions on this initial draft and its validation, and finalizing main ethical components in emergency medicine. In this study, we received the opinions of an expert panel including 10 medical ethicists and 12 emergency medicine specialists using a survey form. Results: The ethical guide to emergency medicine can be formulated in 34 key ethical concepts, 6 sub-components, and 5 main components including emergency physician-patient relationship, and emergency physicians’ relationships with other professionals, students, researchers, and community. Conclusion: Emergency care providers need to be familiar with ethical guidelines in order to improve quality of care in emergency departments. The findings of this study suggest that a guideline on patient-physician relationship as well as the emergency physicians’ ethical obligations for other professionals, students, researchers, and community should be developed in line with ethical norms.